Symulacja semantyczna jako cecha stylu narodowego - Kiklewicz, Aleksander (Stylistyka, 2020)
The author considers the problem of language identity in perspective of its deter- mination by social and cultural factors. In the context of contemporary Eastern Europe (especially Russia), the following factors are taken into consideration: postmodernism, postcommunism, postcolonialism, and state-clan capitalism. The author writes about the paradigm of the simulation as a characteristic of the Russian national identity. Simulation is carried out in the regular use of approximate and non-adequate names, not only in marketing communication, politics and journalism, but also in the sphere of social sciences and the humanities.The author has analyzed some specific cases of aberrative nomination, such as an ‘extramural scientific conference’, ‘university’ or‘cognitive linguistics’.